Financial Determinants of Corporate Value in Indonesia’s Mining Sector: Insights from the Post-COVID Era - Nugroho, Muchamad Aqil; Nugroho, Lucky (Baca Dulu Publisher, 2024)
This study investigates the influence of liquidity, sales growth, leverage, profitability, and company size on the value of mining companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. The research aims to address the problem of inconsistent findings in the existing literature, particularly within the mining sector, by examining these key financial variables' roles in determining company value. Employing a quantitative approach with descriptive and verifiable methods, the study utilizes secondary data from company annual reports, with a sample of 15 companies selected through purposive sampling, resulting in 90 observations. The analysis is conducted using multiple linear regression. The results reveal that leverage, profitability, and company size significantly influence company value, while liquidity and sales growth do not show a significant impact. These findings highlight the importance of effective leverage management and profitability enhancement in boosting company value, especially in the context of the mining sector, which is prone to external economic fluctuations. The study's implications suggest that company management should prioritize strategies that enhance profitability and manage leverage prudently, while also considering the unique challenges faced by larger companies. The novelty of this research lies in its focus on the post-pandemic period, providing new insights into the relationship between financial factors and company value during an era of economic uncertainty.